Morphometrics of two edible frog species [Crowned Bullfrog (Hoplobatrachus occipitalis), and Medine Grassland Frog (Ptychadena pumilio)] in Ibadan, Nigeria (2022)
Edible frog species are integral part of the economy as they are used as an alternative source of protein and are involved in international trade. Conservation efforts on them require information on their morphometry, which is scarce. Therefore, this study documents the preliminary morphometrics of two edible frog species [crowned bullfrog (Hoplobatrachus occipitalis), and medine grassland frog (Ptychadena pumilio)] in Ibadan, Nigeria. Twenty seven (27) live samples of adult H. occipitalis and Six (6) live samples of P. pumilio were used for this study. Live weights (LW) and 15 other external body measurement were taken. Means and standard deviations were computed. The T-tests and Pearson's correlation coefficients were conducted at p<0.05. The LW [52.14+39.58; 22.00+14.20] and Snout-vent length (SVL) [7.83±2.19; 7.00±2.00] in H. occipitalis were significantly higher than that of P. pumilio. The LW in H. occipitalis showed significant (p<0.05) positive correlations with all other measured parameters. In P. pumilio, the LW correlates significantly with SVL (r=0.94), head length (HL) (r=0.82), thigh length (THL) (r= 0.86), fore arm length (FLL) (r= 0.86), IOD (r=0.90), eye diameter (ED) (r=0.90) and tympanum diameter (TD) (r=0.90). The highest correlation coefficient (r=0.98) was found between the LW and SVL in H. occipitalis. These two parameters also had a high correlation coefficient (r=0.94) in P. pumilio. This study provides a preliminary data on the morphometrics of two edible frog species (Hoplobatrachus occipitalis and Ptychadena pumilio) in Ibadan, Nigeria. Molecular investigation of the species is recommended as it will further help in their management and conservation.